A new proposal for the use of the focal animal technique in buffaloes in the Eastern Amazon - Silva, Welligton Conceição da; Silva, Jamile Andréa Rodrigues da; Gouveia Júnior, Amauri; de Alvarenga, Adriano Braga Brasileiro; Barbosa, Antônio Vinícius Correa; Silva, Éder Bruno Rebelo da; Pereira dos Santos, Maria Roseane; Lourenço-Júnior, José de Brito; Camargo Júnior, Raimundo Nonato Colares; Silva, André Guimarães Maciel e (Frontiers in Veterinary Science, 2023)
This study aims to present a proposal for using the focal animal recording technique to evaluate the welfare of buffaloes and verify the associations between each behavior and thermal comfort indices, kept in an experimental paddock in Santarém, Pará, Brazil. In total, 10 animals were used, Murrah females. The behavior of the animals was filmed during the day, with the use of three trained observers, for 72 consecutive hours. Climatic variables were collected and the temperature and humidity indices (THI) and the practical index of buffalo comfort climatic conditions (BCCCIp) were determined. The multivariate technique of principal components and Spearman's correlation were used. BCCCIp and THI were outside the thermal comfort zone, at different times of the day. Grazing (P) was more evident in the coldest hours of the day, while rumination was performed in different periods, highlighting the daytime, more frequently performed in the lying position. There was a positive correlation between idle lying behavior and average temperature -Tmed (r= 0.583; p<0.028), THI (r= 0.432; p<0.034) and BCCCIp (r=0.554; p<0.049). There was a positive correlation between grazing and Tmed (r=0.665; p<0.0004) and BCCCIp (r=0.583; p<0.036). Standing idle behavior negatively correlated with Tmed (r= -0.718; p<0.0001), THI (r= -0.522; p<0.008) and BCCCIp (r= -0.8076; p<0.0008). The lying ruminating behavior had a positive correlation with Tmed (r= 0.586; p<0.002), THI (r= 0.477; p<0.018) and with BCCCIp (r= 0.8033; p<0.0009). Furthermore, ruminating while standing correlated positively with Tmed (r= 0.680; p<0.0003). The adaptation of the focal animal technique, evaluating each animal for six minutes with six observers through filming, proved to be efficient to point out different behavior of buffalo raised in the field in the Eastern Amazon, under heat stress at different times of the day.